Dick Tracy's dilemma - Rawlins, John, 1902-1997; Brode, Robert Stepen; Byrd, Ralph, 1909-1952; RKO Pictures; Cinetel Films ([Los Angeles, CA] : RKO Pictures, 1935)
Dick Tracy investigates the theft of a fortune of fur coats, a possible insurance swindle and several murders, all linked to a huge thug who wears a hook in place of his right hand.
Originally released as a motion picture in 1947
Ralph Byrd, Lyle Latelle, Jimmy Conlin.
Cinematographer, Frank Redman; editor, Marvin Coil; music, Paul Sawtell.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 8, 2016).
Keywords: Tracy, Dick (Fictitious character) -- Drama; Comic strip characters in motion pictures; Detective and mystery films; Feature films; Internet videos; Streaming video